2006
DOI: 10.1111/j.1471-4159.2006.04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective processing of neuropeptide precursors in Caenorhabditis elegans lacking proprotein convertase 2 (KPC‐2/EGL‐3): mutant analysis by mass spectrometry

Abstract: Biologically active peptides are synthesized as larger inactive proprotein peptide precursors which are processed by the concerted action of a cascade of enzymes. Among the proprotein convertases, PC2 is widely expressed in neuroendocrine tissues and has been proposed to be the major convertase involved in the biosynthesis of neuropeptides. In this study, we have examined the role of the Caenorhabditis elegans orthologue PC2/EGL-3 in the processing of proprotein peptide precursors. We recently isolated and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(163 citation statements)
references
References 60 publications
7
155
0
1
Order By: Relevance
“…aex-5 encodes a pro-protein convertase and was identified in the same screen that isolated aex-4 (1,12,13). We confirmed that the pro-protein convertase gene is mutated in aex-5(sa23) by sequencing (lesion is C443W) and by genomic fosmid rescue (Fig.…”
Section: Aex-5supporting
confidence: 63%
See 1 more Smart Citation
“…aex-5 encodes a pro-protein convertase and was identified in the same screen that isolated aex-4 (1,12,13). We confirmed that the pro-protein convertase gene is mutated in aex-5(sa23) by sequencing (lesion is C443W) and by genomic fosmid rescue (Fig.…”
Section: Aex-5supporting
confidence: 63%
“…aex-3 and aex-6 regulate synaptic transmission, probably by regulating exocytosis of neurotransmitter: aex-3 is a guanine nucleotide exchange factor that regulates Rab small guanosine triphosphatase function, and aex-6 (also known as rab-27) is a Rab small guanosine triphosphatase that regulates secretory vesicle exocytosis (10,11). aex-5 encodes a pro-protein convertase, an enzyme that is copackaged with propeptides and processes them to make mature secretory molecules (12,13). Lastly, Doi and Iwasaki (12) demonstrated that aex-1 is a distant homologue of the synaptic gene unc-13 (or Munc13), which acts in the intestine to regulate the DMP.…”
Section: T He Caenorhabditis Elegans Defecation Motor Program (Dmp)mentioning
confidence: 99%
“…3,[26][27][28] Recently, SYFDEKKSVPGVLRF-NH 2 was isolated 3,27 and EMPGVLRF-NH 2 was both predicted and isolated 3,27 ; neither was included in the current study. When we tested KSVPGVLRF-NH 2 (a predicted sequence 25 ) and SVPGVLRF-NH 2 (the isolated peptide [26][27][28] ), both peptides were equally potent to activate FLP-18R1b but SVPGVLRF-NH 2 was two fold more potent at the FLP-18R1a receptor (Table I). It is interesting to note that the shorter peptides were more potent than longer peptides and that the most potent was not a C. elegans but an A. suum peptide, AVPGVLRF-NH 2 (EC 50 7.6-13.1 nM).…”
Section: Elegans Gpcr Y58g8a4 Is a Flp-18 Receptor 345mentioning
confidence: 99%
“…Each neuropeptide processing and secretion component controls multiple behavioral programs. Although immunostaining and mass spectrometry studies have shown that egl-3 and egl-21 mutants have significantly reduced levels of mature FMRFamide-related peptides (Jacob and Kaplan, 2003;Husson et al, 2006), there have been no functional studies linking EGL-3, EGL-21, IDA-1, or UNC-31 to any of the C. elegans neuropeptides. Our newly identified male repetitive turning phenotype of the flp mutants provided an opportunity to genetically address the question.…”
Section: Flp Signaling Pathways Regulate Male Turning Behaviormentioning
confidence: 99%